Efficient trapping of RONS in gelatin and physiological solutions. Issue 2 (20th October 2021) - Kutasi, Kinga; Tombácz, Etelka
Abstract: The work aims to determine the long‐term stability of reactive oxygen and nitrogen species (RONS)‐enriched gelatin solutions and of plasma‐activated physiological solutions produced with an atmospheric pressure surface‐wave microwave discharge. It is demonstrated that the H 2 O 2, NO 3 −, and NO 2 − concentrations are quasi‐stable during 1 month of storage in the 0.5%–2% gelatin solutions prepared with plasma‐activated water, Ringer's (PAR), and phosphate‐buffered saline (PAPBS) solutions, respectively, even at acidic pH 4.5–5.5 conditions. The trapping of RONS is attributed to the protein network developed with gelation. The salt content of the physiological solutions influences the RONS creation and deposition, while stabilizes the 6.5 and 7.2 pH, which ensures the stability of the PAR and PAPBS, respectively, for months. Abstract : It is demonstrated that the H 2 O 2, NO 3 −, and NO 2 − concentrations are quasi‐stable during 1 month of storage in the 0.5%–2% gelatin solutions prepared with plasma‐activated water, plasma‐activated Ringer's (PAR), and plasma‐activated phosphate‐buffered (PAPBS) solutions, respectively. The NO 2 − is efficiently trapped even at acidic pH 4.5–5.5 conditions due to the protein network developed with gelation. The stability of the PAR and PAPBS is ensured by the pH 6.5 and 7.2, respectively, for at least 4 months